2011
DOI: 10.1007/s10882-011-9235-3
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Core Symptomatology in Autism Spectrum Disorders across the Lifespan

Abstract: A preponderance of males with autism spectrum disorders (ASD) has been evident since the initial writings on the topic. This male predominance has consistently emerged in all ASD research to date in epidemiological as well as clinical populations. Despite this long recognized gender disparity in ASD, surprisingly there is a paucity of research addressing gender as it relates to core ASD symptom presentation. Gender differences may manifest with regard to symptom domains, severity, breadth, and so forth. The pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 281 publications
2
30
1
Order By: Relevance
“…This is in contrast to Sivertsen et al (2012), who found that girls with autism spectrum problems had fewer sleep difficulties than boys; however, they had only six girls in their sample, and ASD diagnoses were lacking. Our findings of few differences between boys and girls with ASD is consistent with past research showing very few gender differences in ASD when samples are well-matched (Kozlowski & Matson, 2012;May et al, 2012;Pilowsky, Yirmiya, Shulman, & Dover, 1998;Rivet & Matson, 2011;Solomon, Miller, Taylor, Hinshaw, & Carter, 2011).…”
Section: Discussionsupporting
confidence: 92%
“…This is in contrast to Sivertsen et al (2012), who found that girls with autism spectrum problems had fewer sleep difficulties than boys; however, they had only six girls in their sample, and ASD diagnoses were lacking. Our findings of few differences between boys and girls with ASD is consistent with past research showing very few gender differences in ASD when samples are well-matched (Kozlowski & Matson, 2012;May et al, 2012;Pilowsky, Yirmiya, Shulman, & Dover, 1998;Rivet & Matson, 2011;Solomon, Miller, Taylor, Hinshaw, & Carter, 2011).…”
Section: Discussionsupporting
confidence: 92%
“…Similar results were reported in an American study [Schendel & Bhasin, ] and could also be inferred from the results of another Swedish study [Losh, Esserman, Anckarsäter, Sullivan, & Lichtenstein, ]. Studies showed that females with ASD tend to have lower IQ and worse social skills [Rivet & Matson, ], while others hypothesized the presence of more severe genetic impairments in female cases [Schaafsma & Pfaff, ; Zhao et al, ]. These findings suggest that ASD in females might be associated with more profound developmental problems than ASD in males and with a larger extent of harmful environmental and genetic exposures inciting it.…”
Section: Discussionsupporting
confidence: 82%
“…Indeed, worse social, communicative and cognitive functioning has been found in females with ASD than in males with ASD (McLennan et al 1993;Crick and Zahn-Waxler 2003;Carter et al 2007;Banach et al 2009). However, recent findings increasingly show that core symptoms of ASD do not differ by sex (Hartley and Sikora 2009;Horovitz et al 2011;Mayes and Calhoun 2011;Rivet and Matson 2011a). Parents also may expect more socially desired behaviour from girls, and pressure them more to act in more socially appropriate ways than boys.…”
Section: Introductionmentioning
confidence: 99%